Realidade virtual e realidade aumentada aplicada ao ensino de História no ensino médio da escola pública: possibilidades e limitações - Costa, Daniel da Silva (2024)
This dissertation is the result of research developed within the scope of the Professional Master's Degree in History teaching at the Federal University of Sergipe and had as its starting point the following problem question: how virtual and augmented reality resources can contribute to the teaching/learning of History ? Aiming to answer this question, our main objective is to study the potential and limitations of using virtual and augmented reality technology as a pedagogical tool for the History discipline in the public basic education network, taking into account the material and human limitations typical of public schools. Brazilians. In order to achieve this objective, we carried out qualitative participatory research in a public high school in Bahia. To this end, we taught classes using the aforementioned resources and listened to teachers and students about their impressions regarding the use of the aforementioned resources in the school environment. After this research, we consider that augmented and virtual reality resources are known by the majority of teachers, however, a small minority have already used them for pedagogical purposes, despite considering them as tools with pedagogical potential. Among students, these resources received great approval, highlighting elements such as: greater illustration power, increased engagement and promotion of active teaching/learning. We therefore conclude that virtual and augmented reality resources have good potential for use by History teachers, however, we also note a series of precautions and limitations that need to be considered when inserting these resources in the classroom.